Microsecond melting and revitrification of cryo samples with a correlative light-electron microscopy approach - Bongiovanni, Gabriele; Harder, Oliver F.; Drabbels, Marcel; Lorenz, Ulrich J. (Frontiers in Molecular Biosciences, 2022)
We have recently introduced a novel approach to time-resolved cryo-electron microscopy (cryo-EM) that affords microsecond time resolution. It involves melting a cryo sample with a laser beam to allow dynamics of the embedded particles to occur. Once the laser beam is switched off, the sample revitrifies within just a few microseconds, trapping the particles in their transient configurations, which can subsequently be imaged to obtain a snap shot of the dynamics at this point in time. While we have previously performed such experiments with a modified transmission electron microscope, we here demonstrate a simpler implementation that uses an optical microscope. We believe that this will make our technique more easily accessible and hope that it will encourage other groups to apply microsecond time-resolved cryo-EM to study the fast dynamics of a variety of proteins.